2009
DOI: 10.1080/00071660902758981
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin C and E supplementation on heat shock protein 70 response of ovary and brain in heat-stressed quail

Abstract: 1. The effects of vitamin C (L-ascorbic acid) and vitamin E (alpha-tocopherol acetate) supplementation on egg production and heat shock protein 70 (Hsp70) response of ovary and brain in the Japanese quail (Coturnix coturnix japonica) exposed to high ambient temperature were evaluated. 2. The birds (n = 540; 55 d old) were randomly assigned to 18 groups consisting of 3 replicates of 10 birds each in a 2 x 3 x 3 factorial arrangement of treatments. Birds were kept in wire cages in a temperature-controlled room a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…Dietary manipulations are therefore among the methods used to alleviate these negative adverse effects of environmental stress. Several studies have shown that antioxidant nutrient supplementation is effective in preventing the deleterious effects of heat stress and that these types of nutrients could be included in diets to alleviate the negative effects of heat stress 2,8,9,12 . Vitamin E has been shown to be curative for reproductive tissues in several species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dietary manipulations are therefore among the methods used to alleviate these negative adverse effects of environmental stress. Several studies have shown that antioxidant nutrient supplementation is effective in preventing the deleterious effects of heat stress and that these types of nutrients could be included in diets to alleviate the negative effects of heat stress 2,8,9,12 . Vitamin E has been shown to be curative for reproductive tissues in several species.…”
Section: Discussionmentioning
confidence: 99%
“…The HSP superfamily includes a number of different molecular-weight-class families: HSP110, HSP90, HSP70, HSP60, HSP47, and a group of small HSP ranging from 16 to 40 kDa. They make up approximately 5-10% of the total protein content of cells under conditions of normal, healthy growth 19 and are expressed or increased in response to various biological stressors, such as heat 2,8,9 , malignant tumors 21 , inflammation 22 , viral infections and exposure to toxic chemicals 17,18 . These processes are also involved in the production of ROS, suggesting that oxidative stress is a key mechanism mediating HSP induction 23 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…58 It has been reported that serum HSP-70 levels increased in poultry subjected to HS and also indicated that the decrease in spermatagonic cells in testis of the stressed group is due to the repression in HSP-70 levels. 59 The HSPA1A was up-regulated following HS in Sahiwal heifer. 60 A strong relationship was also established between chicken and HSP 70 genotypes during heat resistance and several studies revealed that there are some polymorphism sites that can be effectively used to identify the heat tolerant trait in chicken respectively.…”
Section: Types Of Hsps Studied In Livestock During Hsmentioning
confidence: 99%